2004
DOI: 10.1002/art.20050
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthetic, nonpsychoactive cannabinoid acid (HU‐320) with antiinflammatory properties in murine collagen‐induced arthritis

Abstract: Objective. To explore the antiarthritic potential of a novel synthetic cannabinoid acid, Hebrew University-320 (HU-320), in the DBA/1 mouse model of arthritis, and to investigate in vitro antiinflammatory and immunosuppressive effects of HU-320 on macrophages and lymphocytes.Methods. DBA/1 mice were immunized with bovine type II collagen (CII) to induce arthritis and then injected intraperitoneally daily with HU-320. The effects of treatment on arthritic changes in hind feet were assessed clinically and histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 52 publications
2
88
0
4
Order By: Relevance
“…juresianum, is completely inactive. This finding is somewhat unexpected as E-caryophyllene has been reported to exert anti-inflammatory effects by activating cannabinoid CB2 receptors (Bento et al, 2011;Medeiros et al, 2007) and endogenous and synthetic cannabinoids have been reported to decrease inflammation in animal models of arthritis (Sumariwalla et al, 2004) and to inhibit IL-1-induced NO production in bovine chondrocytes (Mbvundula et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…juresianum, is completely inactive. This finding is somewhat unexpected as E-caryophyllene has been reported to exert anti-inflammatory effects by activating cannabinoid CB2 receptors (Bento et al, 2011;Medeiros et al, 2007) and endogenous and synthetic cannabinoids have been reported to decrease inflammation in animal models of arthritis (Sumariwalla et al, 2004) and to inhibit IL-1-induced NO production in bovine chondrocytes (Mbvundula et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…1) is usually the most abundant nonpsychoactive cannabinoid in the plant, and it and analogs of CBD have been studied more extensively in recent years. Thus, CBD reduces joint inflammation in collagen-induced arthritis (CIA) in mice (11) and carrageenan paw edema in rats (12). CBD treatment also suppressed release of tumor necrosis factor (TNF)α from synovial cells isolated from the mice.…”
Section: Phytocannabinoids: Tetrahydrocannabinol and Cannabidiolmentioning
confidence: 99%
“…The effect of treatment on infiltration of inflammatory cells known to express C5aR into the paws was investigated by immunohistochemistry on the most severely affected paw from each mouse in the anti-mC5aR-treated group and its isotype control group [34]. Macrophages were detected with anti-F4/80 and neutrophils with anti-Ly6B.2, and the analyses were quantified by digitalized image analysis.…”
Section: Impact Of Anti-mc5ar Treatment On Joint Inflammation and Joimentioning
confidence: 99%